Analysis of Social and Economic Inequality in Access to Health Services: A Case Study in an Urban Area - Muhtar, Muhtar; Tuhumury, Joana Joanitha; Khairunnisa, Atikah; Fretes, Judy De (Socious Journal, 2024)
This research highlights the importance of research into socio-economic inequality in Indonesia, particularly in Maluku Province, with a focus on Buru Village. This research uses qualitative methods, namely observation and interviews, to explore the impact of economic equalization policies on socio-economic inequality at the local level. From September 2022 to March 2023, there was a decrease in the Gini Ratio, which shows a positive indication of economic equalization efforts. However, the impact of this decline was unevenly distributed between urban and rural areas. The results of this study show that although Maluku Province is classified as low in economic inequality by World Bank standards, there are significant challenges that need to be addressed to prevent a potential increase in inequality in the future. The analysis highlights that factors such as access to resources, economic opportunities, and infrastructure differences between urban and rural areas are key elements affecting economic distribution in Maluku. The research provides policy recommendations to improve inclusiveness in economic growth, with the aim of achieving more equitable and sustainable development across the province. Recommendations include improved access to education and training, better economic infrastructure in rural areas, as well as policies that support the development of micro, small and medium enterprises (MSMEs) as a key driver of local economic growth. As such, this research not only provides a deeper understanding of the dynamics of socio-economic inequality in Maluku but also offers concrete solutions to redress existing economic disparities and promote inclusive growth for all communities in the region